Development and Perspective of Gold and Silver Jewelry Imports to Slovakia Considering the Impact of the COVID-19 Pandemic - Tirpáková, Anna; Vojteková, Jana; Opálená, Iveta; Petrovič, František; Repaská, Gabriela; Vojtek, Matej (Anuário do Instituto de Geociências, 2024)
This study focuses on gold and silver jewelry import to Slovakia between the years 2010–2022 for hallmarking according to the country of origin. The aim of the research was to analyze and predict the import of gold and silver jewelry to Slovakia using statistical methods, namely the correlation coefficient and time series analysis. Using the correlation coefficient, we determined the relationship or degree of relation between selected countries of origin based on the amount of gold and silver jewelry (in kg) imported to Slovakia for hallmarking. We obtained an estimate of the future development trend of gold and silver imports into the domestic market from abroad using the time series method, particularly regression analysis and Holt-Winterson methods. It was found that the import of gold jewelry to Slovakia from the studied countries has an upward trend and, conversely, the import of silver jewelry has a downward trend.